Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 94184 by MJS last updated on 17/May/20

∫((x((x−a))^(1/3) )/((x−b))^(1/3) )dx=?  ∫(((x−a))^(1/3) /(x((x−b))^(1/3) ))dx=?

xxa3xb3dx=?xa3xxb3dx=?

Commented by MJS last updated on 17/May/20

I can solve both but I want to know if there's an easier path. will post my solutions later.

Answered by  M±th+et+s last updated on 04/Jun/20

∫x((1−((a−b)/(x−b))))^(1/3) dx,((a−b)/(x−b))=u^3 ⇒dx=(((a−b)(3u^2 ))/((1−u^3 )^2 ))du  I=∫[((a−b)/(1−u^3 ))+b][(((a−b)(3u^2 ))/((1−u^3 )^2 ))](u)du  =(a−b)^2 ∫((3u^2 )/((1−u^3 )^3 ))du+b(a−b)∫((3u^2 )/((1−u^3 )^2 ))du  I_1 =(1/2)∫[(u)(((2)(3u^2 ))/((1−u^3 )^3 ))+(1/((1−u^3 )^2 ))−(1/((1−u^3 )^2 ))]du  I_1 =(1/2)∫d((u/((1−u^3 )^2 )))−(1/2)∫(du/((1−u^3 )^2 ))du  I_3 =∫((1−u^3 +u^3 )/((1−u^3 )^2 ))du=∫(1/(1−u^3 ))du+(1/2)∫((−2u−(1/u^2 )+(1/u^2 ))/([(1/u)−u^2 ]^2 ))du  I_3 =∫(1/((1−u)(1+u+u^2 )))du−(1/2)∫((−(1/u^2 )−2u)/([(1/u)−u^2 ]^2 ))du−(1/2)∫(1/(u^2 [(1/u)−u^2 ]^2 ))du  I_3 =∫((1/3)/(1−u))du+∫(((1/3)u+(2/3))/(u^2 +u+1))du+(1/(2((1/u)−u^2 )))−(1/2)∫(1/((1−u^3 )^2 ))du  I_3 =(1/3)∫d(ln∣1−u∣)+(1/6)∫((2u+1−1)/(u^2 +u+1))du+(2/3)∫(1/(u^2 +u+1))du+(1/(2((1/u)−u^2 )))−(1/2)I_3   (3/2)I_3 =(1/3)ln∣1−u∣+(1/6)ln∣u^2 +u+1∣+(2/3)tan^(−1) (((2u+(1/2))/(√3)))+(1/(2((1/u)−u^2 )))  I_1 =(u/((1−u^3 )^2 ))−(1/2)I_3       I_2 =(3/2)∫((1−u^3 +3u^3 −1)/((1−u^3 )^2 ))du=(3/2)∫((1−u^3 −(u)(−3u^2 ))/((1−u^3 )^2 ))du−(3/2)∫(1/((1−u^3 )^2 ))du  I_2 =(3/2)∫d((u/(1−u^3 )))−(3/2)I_3     I=I_1 +I_2 +c

x1abxb3dx,abxb=u3dx=(ab)(3u2)(1u3)2duI=[ab1u3+b][(ab)(3u2)(1u3)2](u)du=(ab)23u2(1u3)3du+b(ab)3u2(1u3)2duI1=12[(u)(2)(3u2)(1u3)3+1(1u3)21(1u3)2]duI1=12d(u(1u3)2)12du(1u3)2duI3=1u3+u3(1u3)2du=11u3du+122u1u2+1u2[1uu2]2duI3=1(1u)(1+u+u2)du121u22u[1uu2]2du121u2[1uu2]2duI3=131udu+13u+23u2+u+1du+12(1uu2)121(1u3)2duI3=13d(ln1u)+162u+11u2+u+1du+231u2+u+1du+12(1uu2)12I332I3=13ln1u+16lnu2+u+1+23tan1(2u+123)+12(1uu2)I1=u(1u3)212I3I2=321u3+3u31(1u3)2du=321u3(u)(3u2)(1u3)2du321(1u3)2duI2=32d(u1u3)32I3I=I1+I2+c

Answered by mathmax by abdo last updated on 04/Jun/20

let I =∫ (1/x)(^3 (√((x−a)/(x−b))))dx changement^3 (√((x−a)/(x−b)))=t give ((x−a)/(x−b)) =t^3  ⇒  x−a =t^3 x−bt^3  ⇒(1−t^3 )x =a−bt^3  ⇒x =((a−bt^3 )/(1−t^3 )) =((bt^3 −a)/(t^3 −1))  (dx/dt) =((3bt^2 (t^3 −1)−3t^2 (bt^3 −a))/((t^3 −1)^2 )) =((3bt^5 −3bt^2 −3bt^5 +3at^2 )/((t^3 −1)^2 )) ⇒  I =∫  ((t^3 −1)/(bt^3 −a))×t ×(((3a−3b)t^2 )/((t^3 −1)^2 )) dt =(3a−3b) ∫  (t^3 /((bt^3 −a)(t^3 −1)))dt  =((3a−3b)/b) ∫  (t^3 /((t^3 −(^3 (√(a/b)))^3 )(t^3 −1)))dt   let α =^3 (√(a/b)) ⇒  I =((3a−3b)/b) ∫  (t^3 /((t^3 −α^3 )(t^3 −1)))dt let decompose  F(t) =(t^3 /((t^3 −α^3 )(t^3 −1))) ⇒F(t) =(t^3 /((t−α)(t^2  +αt +α^2 )(t−1)(t^2 +t +1)))  =(a/(t−α)) +(b/(t−1)) +((ct +d)/(t^2  +αt +α^2 )) +((et +f)/(t^2  +t+1)) ⇒  ∫ F(t)dt =aln∣t−α∣ +bln∣t−1∣ +∫ ((ct +d)/(t^2  +αt +α^2 ))dt +∫  ((et +f)/(t^2 +t +1))dt  rest to calculate the coefficients...be continued...

letI=1x(3xaxb)dxchangement3xaxb=tgivexaxb=t3xa=t3xbt3(1t3)x=abt3x=abt31t3=bt3at31dxdt=3bt2(t31)3t2(bt3a)(t31)2=3bt53bt23bt5+3at2(t31)2I=t31bt3a×t×(3a3b)t2(t31)2dt=(3a3b)t3(bt3a)(t31)dt=3a3bbt3(t3(3ab)3)(t31)dtletα=3abI=3a3bbt3(t3α3)(t31)dtletdecomposeF(t)=t3(t3α3)(t31)F(t)=t3(tα)(t2+αt+α2)(t1)(t2+t+1)=atα+bt1+ct+dt2+αt+α2+et+ft2+t+1F(t)dt=alntα+blnt1+ct+dt2+αt+α2dt+et+ft2+t+1dtresttocalculatethecoefficients...becontinued...

Answered by MJS last updated on 05/Jun/20

∫((x((x−a))^(1/3) )/((x−b))^(1/3) )dx=       [t=(((x−a))^(1/3) /((x−b))^(1/3) ) → dx=(3/(a−b))(x−a)^(2/3) (x−b)^(4/3) ]  =3(a−b)∫((t^3 (bt^3 −a))/((t^3 −1)^3 ))dt=       [Ostrogradski]  =((a−b)/(6(t^3 −1)^2 ))((a−7b)t^3 +2(a+2b))t+(((a−b)(a+2b))/3)∫(dt/(t^3 −1))=  and I have shown that  ∫(dt/(t^3 −1))=(1/6)ln (((t−1)^2 )/(t^2 +t+1)) −((√3)/3)arctan (((√3)(2t+1))/3)

xxa3xb3dx=[t=xa3xb3dx=3ab(xa)2/3(xb)4/3]=3(ab)t3(bt3a)(t31)3dt=[Ostrogradski]=ab6(t31)2((a7b)t3+2(a+2b))t+(ab)(a+2b)3dtt31=andIhaveshownthatdtt31=16ln(t1)2t2+t+133arctan3(2t+1)3

Answered by MJS last updated on 05/Jun/20

∫(((x−a))^(1/3) /(x((x−b))^(1/3) ))dx=       [t=(((x−a))^(1/3) /((x−b))^(1/3) ) → dx=(3/(a−b))(x−a)^(2/3) (x−b)^(4/3) dt]  =3(a−b)∫(t^3 /((t^3 −1)(bt^3 −a)))dt=       [let a=bc^3  ⇔ c=((a/b))^(1/3) ]  =3(c^3 −1)∫(t^3 /((t^3 −1)(t^3 −c^3 )))dt=  =c∫(dt/(t−c))−∫(dt/(t−1))−c∫((t+2c)/(t^2 +ct+c^2 ))dt+∫((t+2)/(t^2 +t+1))dt=  ...  =(1/2)ln ((t^2 +t+1)/((t−1)^2 )) +(c/2)ln (((t−c)^2 )/(t^2 +ct+c^2 )) +       +(√3)arctan (((√3)(2t+1))/3) −c(√3)arctan (((√3)(2t+c))/3)

xa3xxb3dx=[t=xa3xb3dx=3ab(xa)2/3(xb)4/3dt]=3(ab)t3(t31)(bt3a)dt=[leta=bc3c=ab3]=3(c31)t3(t31)(t3c3)dt==cdttcdtt1ct+2ct2+ct+c2dt+t+2t2+t+1dt=...=12lnt2+t+1(t1)2+c2ln(tc)2t2+ct+c2++3arctan3(2t+1)3c3arctan3(2t+c)3

Terms of Service

Privacy Policy

Contact: info@tinkutara.com